DIVERSIDADE DE VISITANTES FLORAIS EM AMBIENTES URBANOS NO MUNICÍPIO DE MACEIÓ – AL - Lima, Mauricio Silva de; Agra, Virgílio Wanderley Nepomuceno; Agra, Janaina Uchôa Medeiros; Figueiroa, Leonara Evangelista de (Revista Nordestina de Zoologia, 2019)
Floral visitors play an important role in the process of plant maintenance and reproduction. Since these plants depend on such pollinators to perpetuate themselves, urban green areas can fulfill an important ecological role for floral visitors, providing food resources and shelter for their offspring. The objective of this study was to inventory floral visitors of forest remnants in the city of Maceió. Four urban green areas with flowering plants were selected, which allowed to detect the presence and action of floral visitors. Observations were made during the day, in the afternoon. A total of 154 insects belonging to five orders, Hymenoptera, Coleoptera, Diptera, Hemiptera and Lepidoptera was observed. The green areas of Maceió have shown to be important maintainers of several native insect species, even in areas of great impact of vehicles traffic. The present work highlights the importance of studying the urbanization process and how this process can minimize possible impacts caused to the diversity of floral visitors